Maternal Outcomes with Twelve Hour versus Twenty Four Hour Maintenance Doses Of Magnesium Sulfate in Severe Postpartum Preeclampsia - Dwi Putri, Ratu Astuti; Suhaimi, Donel; Hamidy, Yulis; Zulmaeta; Febriani; Yusuf, Muhammad (Indonesian Socety of Obstetrics and Gynecology, 2025)
Introduction: Severe preeclampsia is a serious emergency that can complicate pregnancy and even lead to maternal death. It contributes to a significant increase in morbidity and mortality rates, affecting over 70,000 mothers. The cause of severe preeclampsia is still uncertain, but its management is continuously being developed to achieve the best possible outcomes for both the mother and baby. Magnesium sulfate (MgSO4) is the preferred treatment for preventing seizures in severe preeclampsia, as it has minimal side effects and is effective. However, there is a need for further research on reducing the duration of MgSO4 administration in Indonesia. Method: A clinical trial was carried out with 80 participants divided into two groups (control and trial), using randomized and double-blind methods. The study was conducted at multiple hospitals including Arifin Achmad Hospital, Tengku Rafian Hospital, Dumai City Hospital, Selasih Hospital, and Bengkalis Hospital from October 2022 to February 2023. The data collected was analyzed to evaluate maternal outcomes for both groups. The study was approved by Ethical Review Board for Medicine and Health and registered with the Thai Clinical Trials Registry (TCTR 20230811008) once the data was assessed. Results: This study examined pregnant women with severe preeclampsia, who were on average 30.98±6.04 years old, with 68.8% having had multiple pregnancies. Their gestational age was 33.37±2.88 weeks and the majority (72.5%) had a cesarean delivery. Their systolic blood pressure was 167.68±14.24mmHg and diastolic was 110.32±18.52mmHg. The study did not report on the incidence of eclampsia or maternal mortality, and there was no significant difference in serum magnesium sulfate levels between the two groups (p>0.005). Conclusions: Administering maintenance doses of MgSO4 for both 12 and 24 hours had similar effectiveness in preventing eclampsia, but the 12-hour group saw better outcomes for the mother. Keywords: Magnesium sulfate, Postpartum, Severe preeclampsia, 12 hours, 24 hours